2008
DOI: 10.1002/pam.20324
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of abstinence education on teen sexual activity, risk of pregnancy, and risk of sexually transmitted diseases

Abstract: This paper examines the impacts of four abstinence-only education programs on adolescent sexual activity and risks of pregnancy and sexually transmitted diseases (STDs). Based on an experimental design, the impact analysis uses survey data collected in 2005 and early 2006 from more than 2,000 teens who had been randomly assigned to either a program group that was eligible to participate in one of the four programs or a control group that was not. The findings show no significant impact on teen sexual activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 7 publications
3
50
0
1
Order By: Relevance
“…Rigorous evaluations of AOUM or abstinence-based curricula have failed to demonstrate efficacy in delaying initiation of sexual intercourse, reducing number of partners, increasing condom use, or promoting secondary abstinence (i.e., cessation of sexual intercourse among sexually experienced youth) (Kirby 2008; Trenholm et al 2008). In contrast to abstinence approaches, a 2012 CDC meta-analysis of 66 comprehensive risk reduction programs for youth showed favorable effects on current sexual activity, frequency of sexual activity, number of sex partners, frequency of unprotected sexual activity, use of protection (either condoms and/or hormonal contraception), pregnancy, and STIs (Chin et al 2012).…”
Section: From “Ab-only” To “Ebi-only”: Us Federal Sexual Health Educamentioning
confidence: 99%
“…Rigorous evaluations of AOUM or abstinence-based curricula have failed to demonstrate efficacy in delaying initiation of sexual intercourse, reducing number of partners, increasing condom use, or promoting secondary abstinence (i.e., cessation of sexual intercourse among sexually experienced youth) (Kirby 2008; Trenholm et al 2008). In contrast to abstinence approaches, a 2012 CDC meta-analysis of 66 comprehensive risk reduction programs for youth showed favorable effects on current sexual activity, frequency of sexual activity, number of sex partners, frequency of unprotected sexual activity, use of protection (either condoms and/or hormonal contraception), pregnancy, and STIs (Chin et al 2012).…”
Section: From “Ab-only” To “Ebi-only”: Us Federal Sexual Health Educamentioning
confidence: 99%
“…2007, Chin et al 2012, Kirby 2008, Trenholm et al 2008). HIV prevention programs for youth take place in a variety of settings including schools, health facilities, the mass media, and communities (e.g., community mobilization and outreach) (Ross et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, most AUM curricula rigorously evaluated in the U.S. or elsewhere have failed to demonstrate efficacy in delaying initiation of sexual intercourse, in reducing number of partners, in increasing condom use, or in promoting secondary abstinence (i.e., cessation of sexual intercourse among sexually experienced youth) (Kirby and Ecker 2009, Mavedzenge et al 2011b, Underhill et al 2007, Chin et al 2012, Kirby 2008, Trenholm et al 2008). Kirby (2008) has suggested that AUM programs often fail to incorporate the characteristics of effective comprehensive curriculum-based programs.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the 2009 AEA's Outstanding Evaluation Award was presented to Mathematica Policy Research Inc., for their study, Evaluation of Abstinence-Only Education Programs (see Trenholm et al, 2008). This comprehensive, nine-year, congressionally mandated study, noted for its rigor, balance, and impact, examined abstinence-only education programs intended to reduce teen pregnancies as well as sexually transmitted diseases.…”
Section: Statistical Significancementioning
confidence: 97%